PENGARUH PELATIHAN SENAM HAMIL TERHADAP PENINGKATAN KETRAMPILAN SENAM HAMIL DI WILAYAH KERJA PUSKESMAS KEDUNGMUNDU SEMARANG - Rose Nurhudhariani; Siti Nur Umariyah Febriyanti; Vita Triani Adi Putri (Universitas Muhammadiyah Semarang, 2015)
The application of pregnant mother class is needed for high risk pregnancy. The materials that was taught in pregnant mother class such as Prenatal Excercise. The benefit of doing Prenatal Exercise is helping a pregnant mother to deliver their baby normally, maintaining body readiness, helping to maintain mom’s & baby’s health, giving a relaxed mind and creating a good mechanical system for baby in and after pregancy. This research was aimed to analize the influence of Prenatal Exercise traininig with Prenatal Exercise skill at Kedungmundu District Health Centre.this research used quantitative design with pre-post test without control group approach. The populations were all pregnant mothers at Kedungmundu District Health Centre, and took samples were 15 pregnant mothers by using accidental sampling technique with Wilcoxon to analize the development of skill before and after Prenatal Exercise training. The result showed the average of rate skill before training was 6,20 with Deviation Standard 1,93. And the rate skill after given training was 8,30 with Deviation Standard 1,52 with p value 0,000 < 0,05. The conclusion is the Prenatal Exercise training with lecturing and demosntration is efective to increase skill of Prenatal Exercise in pregnan mothers at Kedung Mundu District Health Center Semarang.Key Words : Prenatal Exercise, Pregnant Mothers